Modal Sosial dalam Pengembangan Pendidikan Anak Yatim Yabima - Kaisar Atmaja; Amin Jamaludin Lubis (Prodi Sosiologi FISIP Universitas Teuku Umar, 2022)
Tarbiyatul Yatama Foundation (Yabima) is a socio-religious foundation that provides education for orphans in the Purwoyoso, Semarang city. In practice, Yabima utilizes mosques because they do not yet have a boarding house. Meanwhile, the board of Yabima was able to build a boarding house. The implementation and development of Yabima’s orphan's education are used in social capital theory. This paper reveals the form and use of Yabima's social capital in implementing and developing the education of orphans. By using qualitative methods and descriptive approaches, the data in this paper were obtained through observations, interviews, and documentation. This paper shows that social capital in the implementation of education is based on Yabima’s board resources such as a network of authority, trust, and collective values. The board of Yabima utilizes social capital to develop the education of orphans. They actualize the relations of authority they have by coordinating cross-sectoral to develop the education of orphans through the provision of boarding houses, increased resources, and publication of bulletin. The board of Yabima maintains civic trust by periodically submitting Yabima's financial recapitulation. It can be seen from civic participation and also Yabima’s board participation in the wakaf program for the construction of Yabima’s boarding house.